Does White Clover (Trifolium repens) Abundance in Temperate Pastures Determine Sitona obsoletus (Coleoptera: Curculionidae) Larval Populations? - McNeill, Mark R.; van Koten, Chikako; Cave, Vanessa M.; Chapman, David; Hodgson, Hamish (Frontiers in Plant Science, 2016)
To determine if host plant abundance determined the size of clover root weevil (CRW) Sitona obsoletus larval populations, a study was conducted over four years in plots sown in ryegrass (Lolium perenne) (cv. Nui) sown at either 6 or 30 kg/ha and white clover (Trifolium repens) sown at a uniform rate of 8 kg/ha. This provided a range of % white clover content to investigate CRW population establishment and impacts on white clover survival. Larval sampling was carried out in spring (October) when larval densities are near their spring peak at Lincoln (Canterbury, New Zealand) with % clover measured in autumn (April) and spring (September) of each year. Overall, mean larval densities measured in spring 2012, 2013, 2014 and 2015 were 310, 38, 59 and 31 larvae m-2, respectively. There was a significant decline in larval populations between 2012 and 2013, but spring populations were relatively uniform thereafter. The mean % white clover measured in autumns of 2012 to 2015 was 17, 10, 3 and 11%, respectively. In comparison, mean spring % white clover from 2012 to 2015, averaged c. 5% each year. Analysis relating spring (October) larval populations to % white clover measured in each plot in autumn (April) found the 2012 larval population to be statistically significantly larger in the ryegrass 6 kg/ha plots than 30 kg/ha plots. Thereafter, sowing rate had no significant effect on larval populations. From 2013 to 2015, spring larval populations had a negative relationship with the previous autumn % white clover with the relationship highly significant for the 2014 data. When CRW larval populations in spring 2013 to 2015 were predicted from the 2013 to 2015 autumn % white clover, respectively, based on their positive relationship in 2012, the predicted densities were substantially larger than those observed. Conversely, when 2015 spring larval data and % clover was regressed against 2012-2014 larval populations, observed densities tended to be higher than predicted, but the numbers came closer to predicted for the 2013 and 2014 populations. These differences are attributed to a CRW population decline that was not accounted by % white clover changes, the CRW